1997
DOI: 10.1209/epl/i1997-00225-3
|View full text |Cite
|
Sign up to set email alerts
|

Observation of 4d ferromagnetism in free-standing Pd fine particles

Abstract: We report on observation of 4d ferromagnetic ordering in pure Pd fine particles. Results of our dc magnetic measurements as a function of Pd particle size show that the magnetization increases rapidly with decreasing particle size; a sample with 59 Å median radius at 1.8 K under 4 kOe shows a factor of nineteen larger magnetization than that of Pd bulk. We suggest that only the surface monolayers of Pd particles are magnetic. The ferromagnetic moment we deduced based on this assumption is 0.23 ± 0.19μB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 24 publications
4
75
1
1
Order By: Relevance
“…Hence, the experiments can also supply a hint about the magnetic moment per atom if we consider it uniformly distributed over all the particles and over all the atoms of each particle that approximately yields 10 ÿ3 Bohr magnetons per atom. This value is 1 order of magnitude smaller than that experimentally found by Taniyama et al [4], and 2 orders below that theoretically predicted for icosahedral structure [5]. It seems to indicate that probably only a very small fraction of the total number of atoms exhibits permanent magnetic moment and eventually ferromagnetism.…”
Section: P H Y S I C a L R E V I E W L E T T E R Scontrasting
confidence: 48%
See 2 more Smart Citations
“…Hence, the experiments can also supply a hint about the magnetic moment per atom if we consider it uniformly distributed over all the particles and over all the atoms of each particle that approximately yields 10 ÿ3 Bohr magnetons per atom. This value is 1 order of magnitude smaller than that experimentally found by Taniyama et al [4], and 2 orders below that theoretically predicted for icosahedral structure [5]. It seems to indicate that probably only a very small fraction of the total number of atoms exhibits permanent magnetic moment and eventually ferromagnetism.…”
Section: P H Y S I C a L R E V I E W L E T T E R Scontrasting
confidence: 48%
“…Experiments carried out by Taniyama et al [4] in 1997 have evidenced the appearance of a magnetic moment in Pd clusters with an average radius below 7 nm. Furthermore, these authors found ferromagnetic behavior of Pd particles of 5.9 nm average radius with an atomic moment of 0:23 B per surface atom.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this system chlorine atoms form an interstitial layer between the metal core and the surfactant shell. The interstitial chlorine ion is subjected to an attractive electrostatic force toward the N͑alkyl͒ 4 + ion so that the position of the negative ion depends on the alkyl chain length. For very long alkyl chains steric impediments produce a less dense protection shell.…”
Section: A Microstructural and Chemical Characterization Of Npsmentioning
confidence: 99%
“…3 Accordingly, the factors that can affect the onset of ferromagnetism in Pd are those increasing N͑E F ͒ in order to accomplish the Stoner criterion. 4 Experiments carried out by Taniyama et al 4 have evidenced the appearance of magnetic moment in Pd clusters with average radius below 7 nm. Due to the strong surface energy anisotropy, these clusters of Pd exhibit a noncrystallographic icosahedral structure instead of the typical bulk fcc symmetry, which has been identified as the origin of this ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%